The Nanomedicine Revolution: Part 2: Current and Future Clinical Applications - Ventola, C. Lee (MediMedia USA, Inc., 2012)
Although many nanotherapeutic and nanodiagnostic agents are in use and have the potential to improve health care, many barriers have impeded the development and availability of these products. Despite these impediments, it is expected that nanomaterials will become an integral part of mainstream medicine.